Lawyers as leaders - Rhode, Deborah L. (Oxford University Press, 2013)
No occupation in America supplies a greater proportion of leaders than the legal profession, yet it has done little to prepare them for this role. Lawyers sit at the helm of a vast array of powerful law firms, businesses, governmental, and nonprofit organizations. Two of the last three presidents have been lawyers. And yet almost no occupation rouses greater public distrust. This paradox raises two important questions: Why do we look to lawyers to lead, and why do so many of them prove to be so ill-prepared for that role? In Lawyers as Leaders, eminent law professor Deborah Rhode not only answ.